DIGITAL AUDIO PLATFORMS, LEARNER AUTONOMY, AND ENGLISH ACHIEVEMENT: A CORRELATION STUDY IN INDONESIAN VOCATIONAL EDUCATION - Lina Adiniatul Munawaroh; Titik Lina Widyaningsih (Universitas Wiralodra, 2026)
This research examines the correlation between the utilization of digital audio platforms, learner autonomy, and English learning outcomes among tenth-grade students in an Indonesian vocational high school. The study employed a quantitative correlational design, with 33 students chosen by purposive sampling. Data were collected through questionnaires on digital audio platform use and learner autonomy, as well as English report card grades representing learning outcomes. The findings revealed significant positive correlations between digital audio platform use and English learning outcomes (r = 0.701, p < 0.05), and between learner autonomy and English learning outcomes (r = 0.710, p < 0.05). A multiple correlation analysis also showed a strong combined relationship between both variables and English learning outcomes (R = 0.783, p < 0.05). This study contributes to the current literature by examining the synergistic effect of digital audio platforms and learner autonomy in a vocational EFL context. We used report card grades to measure how well students learned English. Report cards show how well students did in school over time, as judged by their teachers. The results suggest that integrating digital audio platforms with learner autonomy strategies can enhance the English proficiency of vocational students.